Dispute resolution on an insurance policy that includes an arbitration clause: a study of award 39/PDT.G/2021/PN PAL - Zihantara, Shehan (Universitas Wiralodra, 2024)
This study aims to determine absolute competence or authority to adjudicate the District Court in insurance disputes with insurance policies that include dispute resolution clauses through arbitration. The method used in this study is the non-doctrinal method. The data/subject matter in this study was obtained directly from respondents through field research, namely architects who had created a work. That an insurance policy that includes an arbitration clause should be resolved through the Arbitration Board in accordance with the policy and this should nullify the authority of the district court to adjudicate a dispute arising as a result of the insurance policy. The clause in the settlement has a function for the company to be able to resolve a problem in private to maintain the good name of the company and resolve the problem in a shorter time when compared to the District Court, because of this, settlement through arbitration is the choice of insurance companies, but in practice Often lawsuits against insurance companies as guarantors agreed with the insurance policy are submitted to the District Court, resulting in discrepancies in the procedure for resolving insurance disputes.